Դաւիթ Քոբայրեցու՝ Եսայու մեկնութեան աղբիւրները - Քէօսէեան, Յակոբ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В настоящей статье подробно анализируются источники толкования на Книгу пророка Исаии, использованные выдающимся армянским книжником XII–XIII вв. Давидом Кобайреци. Особое внимание уделяется отцам Церкви, на которых он опирался — Иоанну Златоусту, Ефрему Сирину и Кириллу Александрийскому. Исследуются принципы и приёмы применения этих источни- ков, что позволяет реконструировать логику и особенности метода библейской интерпретации армянского толкователя. На основе конкретных текстологических данных обосновывается, что вплоть до XII–XIII вв. в армянской церковной литературе широко циркулировали полные версии толкований на Книгу Исаии, приписываемые Ефрему Сирину и Кириллу Александрийскому, которые впоследствии были утрачены. Об этом, в частности, свидетельствуют толкования на ту же книгу, дошедшие под именами Ованнеса, сына Муша, и Геворка Скевраци. This study provides a comprehensive examination of the exegetical sources employed by the eminent Armenian scholar of the 12th–13th centuries, Davit‘ of Kobayr, in his commentary on the Book of the Prophet Isaiah. Special emphasis is placed on the patristic authorities he drew upon—John Chrysostom, Ephrem the Syrian, and Cyril of Alexandria. The article explores the interpretative strategies and methodological approaches through which these sources were integrated, thereby enabling a reconstruction of the underlying logic and distinctive features of Davit‘’s exegetical practice. On the basis of concrete textual evidence, it is argued that, up to the 12th–13th centuries, complete versions of commentaries on Isaiah attributed to Ephrem the Syrian and Cyril of Alexandria were in wide circulation within the Armenian ecclesiastical tradition, though they have since been lost. This claim is further corroborated by extant commentaries on the same prophetic book transmitted under the names of Hovhannes, son of Mush, and Gevork of Skevr.
Keywords: Կրօնագիտական; Վկայութիւններ